Development of Pop-Up Book Media for Science Learning Content for Grade V Students in Elementary School - Fazrin, Khamellisa Qobrina; Winahyu, Sri Estu; Untari, Esti (Journal of Education for Sustainability and Diversity, 2023)
This study aims to produce Pop-Up Book media which are declared valid from the assessment of material experts and media experts as well as interesting learning media according to teachers and students. The need to produce media is to make it easier for teachers to deliver material using media so that the student learning atmosphere is more enjoyable. This research and development were carried out using the reference of the ADDIE model which went through several stages, the first was analysis, the second was design, the third was development, the fourth was implementation, and the last was evaluation. Collecting data researchers used observations in elementary schools, teacher and student interviews, material expert questionnaires, media, teachers, and students. The results obtained from media validation were 98.07% which were categorized as very valid, material validation was 91.34% which were categorized as very valid, teacher validation was 98.07% which was categorized as very practical and interesting, and student attractiveness test was 96. 25% which is categorized as very interesting, and making Pop-Up Book media can be used to assist teachers in delivering material in class.